THE ACOUSTIC FEATURES OF EMPHATICITY IN INDONESIAN - Sugiyono Sugiyono (Kajian Linguistik dan Sastra, 2009)
This study describes prosodic features which marked the emphatic meaning in Indonesian from Indonesian speaker whose mother tongue is, for instance, Javanese, Sundanese, Betawi, Bataknese, Bugisnese, Minangnese, Ma’anyanese, Balinese, and Mandailing. This study is conducted by applying experimental phonetic approach that is by selecting imperative sentences Tutup pintu! ‘Close the door!’ as a target sentence. The data are collected by asking a subject to commend and to repeat the same command to a child or someone who is of the same age of his child to close the door. All collected data are measured in terms of its frequency, intensity, and duration. Those three features are then analyzed statistically to find out the significance differences of acoustic feature difference on every level of utterance emphaticity. The results of this study shows that frequency, intensity, and duration are significant markers which differentiate emphaticity level. In terms of frequency, the higher the emphaticity level ofthe utterance is, the higher the frequency of the base pitch, final pitch, and pitch range of that utterance will be. From the sound intensity point of view, the emphaticity of utterance is marked by base intensity and intensity range. The utterance with high emphaticity level is marked by high base intensity and wider range intensity. From duration point of view, the utterance emphaticity is marked by the duration of all vowels. The height of emphaticity level is marked by the length of time needed by the vowels to be uttered. The emphaticity markers show meaningful correlation.Keywords: acoustic phonetics; experimental phonetics; speech perception; andprosodie feature